Trends in binge drinking and alcohol abstention among adolescents in the US, 2002-2016. (1st July 2019) - Clark Goings, Trenette; Salas-Wright, Christopher P.; Belgrave, Faye Z.; Nelson, Erik J.; Harezlak, Jaroslaw; Vaughn, Michael G.
Highlights: Binge drinking decreased substantially among US adolescents across time. Binge drinking decreased across age, gender, and race/ethnicity. Alcohol abstention increased among US adolescents over the past 15 years. Abstract: Background: Binge drinking accounts for several adverse health, social, legal, and academic outcomes among adolescents. Understanding trends and correlates of binge drinking and alcohol abstention has important implications for policy and programs and was the aim of this study. The current study examined trends in adolescent binge drinking and alcohol abstention by age, gender, and race/ethnicity over a 15-year period. Methods: Respondents between the ages of 12 and 17 years who participated in the National Survey on Drug Use and Health (NSDUH) between 2002 and 2016 were included in the sample of 258, 309. Measures included binge drinking, alcohol abstention, and co-morbid factors (e.g., marijuana, other illicit drugs), and demographic factors. Results: Logistic regression analyses were conducted to examine the significance of trend changes by sub-groups while controlling for co-morbid and demographic factors. Findings indicated that binge drinking decreased substantially among adolescents in the US over the last 15 years. This decrease was shown among all age, gender, and racial/ethnic groups. In 2002, Year 1 of the study, 26% of 17-year-olds reported past-month binge drinking; in 2016, past-month binge drinking dropped to 12%. Findings also indicated comparable increases in the proportion of youth reporting abstention from alcohol consumption across all subgroups. Black youth reported substantially lower levels of binge alcohol use and higher levels of abstention, although the gap between Black, Hispanic and White youth narrowed substantially between 2002 and 2016. Conclusion: Study findings are consistent with those of other research showing declines in problem alcohol- use behavior among youth.